Effectiveness of syndromic management for male patients with urethral discharge symptoms in Amazonas, Brazil - Jonas Rodrigues de Menezes Filho; José Carlos Gomes Sardinha; Enrique Galbán; Valéria Saraceni; Carolina Talhari (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Urethral discharge syndrome (UDS) is characterized by the presence of purulent or mucopurulent urethral discharge.The main etiological agents of this syndrome are Neisseria gonorrhoeae and Chlamydia trachomatis. Objectives: To evaluate the effectiveness of the syndromic management to resolve symptoms in male urethral discharge syndrome cases in Manaus, Amazonas, Brazil. Methods: Retrospective cohort of male cases of urethral discharge syndrome observed at a clinic for sexually transmitted disease (STD) in 2013. Epidemiological and clinical data, as well as the results of urethral swabs, bacterioscopy, hybrid capture for C.trachomatis, wet-mount examination, and culture for N.gonorrhoeae, were obtained through medical chart reviews. Results: Of the 800 urethral discharge syndrome cases observed at the STD clinic, 785 (98.1%) presented only urethral discharge syndrome, 633 (79.1%) returned for follow-up, 579 (91.5%) were considered clinically cured on the first visit, 41(6.5 %) were considered cured on the second visit, and 13(2.0%) did not reach clinical cure after two appointments. Regarding the etiological diagnosis, 42.7% of the patients presented a microbiological diagnosis of N.gonorrhoeae, 39.3% of non-gonococcal and non-chlamydia urethritis, 10.7% of C.trachomatis and 7.3% of co-infection with chlamydia and gonococcus. The odds of being considered cured in the first visit were greater in those who were unmarried, with greater schooling, and with an etiological diagnosis of gonorrhea. The diagnosis of non-gonococcal urethritis reduced the chance of cure in the first visit. Study limitation: A study conducted at a single center of STD treatment. Conclusion: Syndromic management of male urethral discharge syndrome performed in accordance with the Brazilian Ministry of Health STD guidelines was effective in resolving symptoms in the studied population. More studies with microbiological outcomes are needed to ensure the maintenance of the syndromic management.